The gathering - Enright, Anne 1962- (Black Cat, 2007)
As nine members of the Hegarty clan gather for the wake of their drowned brother Liam, his sister Veronica remembers the secret he shared with her about what happened in their grandmother's house thirty years ago, a betrayal that spans three generations.